The Emigré Writers of the Empire : Other Coasts of Russian Literature and Culture: Ideas, Poetics, Contexts. Collective Monograph. Eds. Elżbieta Tyszkowska-Kasprzak, Ilona Motiejunaite and Alfija Smirnova in cooperation with Maria Gej. Scriptum, Wroclaw ‒ Krakow 2021, p. 494 ISBN 978-83-66812-37-6 - Pálfalvi, Lajos (Slavica, 2023)
This volume of studies on Russian émigré literature was published during the last year before the war in a form of scholarly cooperation between Polish, Russian, Ukrainian, and Czech scholars unthinkable today. The theme of joint research makes the work even more interesting, because Poles have a very different understanding of the mission of émigré writers than Russians. In the first chapter of the monograph, entitled The History of Emigration, we find interesting biographical portraits of prominent figures such as Alexander Herzen and Gleb Struve. In the next part we read mainly about ideological problems and ethnic stereotypes. The third chapter focuses on the problems of poetics, and the last on heterotypes. The aspects of the analyses also touch upon the poetics of space and imagology.